Uma análise semântico-pragmática das construções condicional-concessivas no português do Brasil - Cavaguti, Ana Paula (2018)
This research is based on Formal Semantics assumptions and its main goal is to describe the concessive conditional clauses in Brazilian Portuguese. König (1985, 1986) and König and Van Der Van Der Auwera (1988) assert that the concessive conditional clauses share semantic values with the conditional and concessive clauses. In this work, we assume that the concessive conditionals clauses represent a distinct category with specific properties that distinguish them from conditional and concessive clauses. In this research, we propose to investigate: (i) the logical relations and their values of truth that manifested in the concessive conditionals clauses; (ii) the operators that express the concessive conditional meaning; (iii) the features of modality proposed by Kratzer (1981, 2010); (iv) the order of the concessive conditionals clauses in relation to the main clause, (v) the verbal tenses correlations of the both clauses and (vi) identify the type of content suggested that is manifested in the concessive-conditionals. Regarding to item (i), the concessive conditionals clauses can be represented by the logical form (p ˅ ¬p) → q. In relation to the truth conditions, the truth value of p was identified on the basis of the disjunction that manifests in p, that this proposition can be true in two distinct worlds; q is always true in all accessible worlds. With respect to goal in (ii), we identified that, beyond the concessive conditional adverbial clauses, there are non-canonical structures that can also convey, pragmatically, the concessive conditional value. Concerning modality features in (iii), it was found that the modal strength of necessity is determined by the indicative mode; the modal basis may be given by an buletic, deontic, epistemic or teleological conversational background. The ordering of the worlds varies according to the information of the nuclear sentence. With respect to item (iv), it was found that only in the sentences beginning with ACID nem se/nem que, the inversion of the order of the adverbial sentence in relation to the nuclear sentence, interferes in the polarity of the nuclear sentence. In other adverbial constructions, we can change the sentences, without prejudice to meaning. In constructions with adversative ACIDs, the clause initiated with this operator is always follows to the asynthetic sentence. Toward relation of tense verbs - (v) that configures the concessive conditional, it was identified that in the clause in which there is the possibility operator can be expressed with the subjunctive (explicit or not) or with the gerund, and the nuclear, with the indicative mode. Concerning goal in (vi), it has been proved by tests that the secondary content that manifests itself in this type of construction is a conventional implicature, triggered by ACIDs, according to Bach (1999).